Low-Complexity Analog Linear Coding Scheme - Insausti, Xabier; Crespo, Pedro M.; Gutierrez-Gutierrez, Jesus; Zarraga-Rodriguez, Marta (IEEE communications letters, 2018)
In this letter, we design a low-latency, low-complexity, and low-transmission power analog linear coding scheme to estimate the finite-length data blocks under a mean-square-error (distortion) criterion. The proposed scheme is based on the analog linear coding and the discrete Fourier transform. A remarkable feature of our scheme is that it does not require knowing the correlation matrix of the data blocks, and therefore, it can be used even if the correlation matrix changes slowly with time.